The structure, conformation, and hypoglycemic activity of a novel heteropolysaccharide from the blackberry fruit. Issue 12 (17th May 2021) - Dou, Zu-Man; Chen, Chun; Huang, Qiang; Fu, Xiong
Abstract : A novel heteropolysaccharide fraction (BBP-24-3) with a relative molecular weight of 145.1 kDa was isolated from blackberry fruits. Abstract : A novel heteropolysaccharide fraction (BBP-24-3) with a relative molecular weight of 145.1 kDa was isolated from blackberry fruits. The BBP-24-3 was mainly composed of arabinose, glucose, and galacturonic acid with a ratio of 5.30 : 3.60 : 91.10 mol%. Structural analysis showed that BBP-24-3 possessed a 1, 6-linked β-d -Glcp, 1, 2, 3, 5 linked α-l -Araf, and 1, 4 linked α-d -GalpA backbone with branches substituted at the C-2 and C-5 positions of arabinose units, which included 1, 2, 3, 4 linked β-d -Glcp and T-linked β-d -GalpA. The conformation analysis indicated that BBP-24-3 exhibited a solid spherical structure with a uniform distribution in 0.1 M NaCl solution. The BBP-24-3 exhibited excellent α-glucosidase inhibitory activity with an IC50 value of 3.70 mg mL −1, which was due to the structural change, including α-helix and random coil of α-glucosidase caused by BBP-24-3. The current work suggests the potential utilization of BBP-24-3 as an α-glucosidase inhibitor in healthy food for reducing the postprandial blood glucose level.